Heterogeneous Pulmonary Perfusion on Dual-Energy Computed Tomography: Faulty Postprocessing or New Artifact?. Issue 6 (November 2018) - Borse, Riddhi; Homayounieh, Fatemeh; Singh, Ramandeep; Digumarthy, Subba R.
Abstract : Abstract: Iodine uptake in the lungs and intrathoracic lesions on postcontrast dual-energy computed tomography is used for evaluation of pulmonary embolism–related perfusion defects and pulmonary infarctions. It has been applied in characterization and treatment response assessment of lung and mediastinal abnormalities. We report a new imaging artifact or faulty image postprocessing in a commercially available rapid kV switching technique of dual-energy computed tomography, which can confound its clinical utility for evaluation of iodine uptake.